2022
DOI: 10.21608/ejchem.2022.121196.5481
|View full text |Cite
|
Sign up to set email alerts
|

Study the mammalian acute toxicity of sodium yttrium fluoride, erbium and ytterbium doped (NaYF4: Er3+, Yb3+) upconversion nanomaterials

Abstract: The potential toxicity and biocompatibility of sodium yttrium fluoride, erbium and ytterbium doped (NaYF4: Er 3+ , Yb 3+ ) upconversion nanoparticles are of great importance for their biomedical applications. In this work, the acute toxicity of sodium yttrium fluoride, erbium and ytterbium doped (NaYF4: Er 3+ , Yb 3+ ) upconversion nanomaterials toxicity was evaluated. Rats received intravenous injection of 10 mg/kg of NaYF4: Er 3+ , Yb 3+ doped upconversion nanoparticles once dose and were observed at two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Lastly, the concerns that have been expressed about the toxicity of YbF 3 [11,18] do not seem to be supported by the published evidence on the effect of trace amounts of the substance on humans [12,54]. However, given the use described in this review in dental materials, this lack of clarity about toxicity is concerning, and further studies on this topic are clearly desirable as well.…”
Section: The Chemical Behaviour Of Ytterbium Fluoride When Used In De...mentioning
confidence: 86%
See 1 more Smart Citation
“…Lastly, the concerns that have been expressed about the toxicity of YbF 3 [11,18] do not seem to be supported by the published evidence on the effect of trace amounts of the substance on humans [12,54]. However, given the use described in this review in dental materials, this lack of clarity about toxicity is concerning, and further studies on this topic are clearly desirable as well.…”
Section: The Chemical Behaviour Of Ytterbium Fluoride When Used In De...mentioning
confidence: 86%
“…However, any reported toxicity appears to be low. For example, a recent study found no obvious toxicity over 14 days following the exposure of rats to nanoparticles doped with Yb 3+ ions [12]. Also, safety data sheets provided by companies typically claim that ytterbium fluoride lacks any significant toxicity [13,14].…”
Section: Ytterbium Compoundsmentioning
confidence: 99%
“…However, no significant toxicity was detected after high dose exposure for 14 days in mice. On the other hand, Shahba et al 73 also studied the mammalian acute toxicity of NaYF 4 :Er 3+ ,Yb 3+ and found no obvious signs of abnormality within 14 days in mice after injection. Despite that the acute toxicity of UCNPs was proved to be insignificant in the mentioned study, more in vivo evaluation with long-term toxicity still needs to be carried out to verify the bioavailability of UCNPs.…”
Section: Disease Treatment Using Upconversion Nanoparticlesmentioning
confidence: 99%
“…Er-doped NaYF 4 crystals can be used for similar applications as Yb-doped crystals but they emit light in the infrared region of the spectrum, making them particularly useful for applications in the field of optical communications [17,18]. Both Yb and Er doped NaYF 4 (NaYF 4 :Yb,Er) crystals are relatively new research area, and scientists are actively investigating new ways to improve the performance of these crystals and find new application for them [19][20][21]. In recent years, researchers have used the (NaYF 4 :Yb,Er) in the optoelectronic devices such as photovoltaic cells and sensor [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%